Book review / Information models for assessment and management of development trends - Lenz, Barbara (Technological and Economic Development of Economy, 2008)
Reviewed book: Vitalija RUDZKIENĖ, Marija BURINSKIENĖ. Plėtros krypčių vertinimo ir valdymo informaciniai modeliai: monografi ja. Vilnius: Technika, 2007 [Information Models for Assessment and Management of Development trends] in Lithuanian. First published online: 21 Oct 2010